Association between alcohol consumption and colorectal cancer risk: a case–control study in the Han Chinese population. Issue 5 (September 2018) - Wang, Yue; Yang, Helen; Shen, Chun-Jian; Ge, Jin-Nian; Lin, Jie
Abstract : Many epidemiologic studies have reported that alcohol is a risk factor for colorectal cancer. To further evaluate the association, we carried out a case–control study in the Han Chinese population. From February 2008 to February 2013, we carried out a hospital-based case–control study on colorectal cancer. Information was collected using a questionnaire. Cases were 310 patients with colorectal cancer; 620 healthy matched controls were also recruited. Multiple logistic regression was used to estimate the odds ratios (OR) and the corresponding 95% confidence intervals. Alcohol consumption was associated with increased colorectal cancer risk, but OR was significant only among heavy drinkers (OR=2.18, for ≥21 drinks/week). Colorectal cancer risk was 4.01-fold higher in heavy smokers (≥20 cigarettes/day) and heavy drinkers (≥21 drinks/week) in comparison with never smokers who consumed less than 7 drinks/week. The relationship was strengthened by stratified studies of sex. Among former drinkers, the excess of risk disappeared in those who had quit for at least 10 years (OR=0.86). Our study confirmed that heavy alcohol consumption was associated with an increasing risk of colorectal cancer; smoking modified this relationship, especially heavy smokers. Further data from large cohorts are desirable for conclusive confirmation.